El autoempleo de las trabajadoras inmigradas. ¿Una alternativa a la discriminación laboral? - Solé, Carlota; Parella, Sònia; Alarcón, Amado (Cuadernos de Relaciones Laborales, 2009)
This paper analizes, from a gender perspective, the motivations on the burgeoning development of noncomunitarian migrant women business in Spain. These women decide to become entrepreneurship after long labour trajectories mainly at the domestic service and other labour activities connected with social reproduction and care. We link these activities both to the role of the social networks of immigrants themselves and to the conditioning factors of the economic structures of the host society. The main objective is to study, through qualitative interview technique, if the entrepreneurial decision is a reaction to their marginal position on the labour market, in terms of wages, labour conditions and social status; as well as a reaction to their frustration once they realize labour mobility is difficult.